Efektivitas E-Logistik dan Tele-Logistik dalam Optimalisasi Pengelolaan Logistik Keperawatan di Ruang Rawat Inap: Suatu Program Inovasi - Eva Eva; Rr. Tutik Sri Hariyati; Desnita Fitri (Journal of Telenursing (JOTING), 2022)
This study aims to describe an innovation program in optimizing nursing logistics management. The method used is in the form of an innovation program through a problem solving approach that starts from problem identification, problem analysis with fishbone diagrams, preparation of POA, implementation with PDCA, evaluation and gap analysis with literature review. The innovation program was applied to the head of the room, team leader and implementing nurses totaling 108 people recruited by purposive sampling using questionnaires, interviews and observations. The results of the study indicate that: 1) the identification stage, still needs to be done to improve the management of nursing logistics; 2) the evaluation stage, E-Logistics and Tele-Logistics can be used as a planning and controlling instruments, simplify the logistics planning process, can prevent stockouts and overstocks, simplify the linen handover system, improve the quality of nursing care. In conclusion, E-Logistics and Tele-Logistics help improve the implementation of nursing logistics management. Keywords: E-Logistics, Optimizing Logistics Management, Tele-Logistics